Determinants of food demend among rural households in Borno state, Nigeria - Amaza, P.; Fregene, T. (2008)
This study uses a food consumption survey of rural households to examine the determinants of food demand in Borno State, Nigeria. The Linear-Approximate Almost Idea Demand System (LA/AIDS) model was used in analysis of data. Results showed that the income elasticities (expenditure) for animal protein and fat & oil are positive but greater than one, while those of cereals, legumes, roots & tubers and vegetables & fruits were less than one but positive. The policy implication of this finding is that due to the high cost of animal protein, it is important to introduce new recipe of legume-based food in order to supplement protein intake.